2014
DOI: 10.1002/cam4.373
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of triplet regimen antiemetic therapy for chemotherapy‐induced nausea and vomiting (CINV) in bone and soft tissue sarcoma patients receiving highly emetogenic chemotherapy, and an efficacy comparison of single‐shot palonosetron and consecutive‐day granisetron for CINV in a randomized, single‐blinded crossover study

Abstract: The first aim of this study was to evaluate combination antiemetic therapy consisting of 5-HT3 receptor antagonists, neurokinin-1 receptor antagonists (NK-1RAs), and dexamethasone for multiple high emetogenic risk (HER) anticancer agents in bone and soft tissue sarcoma. The second aim was to compare the effectiveness of single-shot palonosetron and consecutive-day granisetron in a randomized, single-blinded crossover study. A single randomization method was used to assign eligible patients to the palonosetron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The results revealed that the anti-emetic effects of granisetron last only a relatively short time when the drug is administered once or even twice per day; however, the effects of palonosetron persist over its long plasma elimination half-life, which facilitates continuous supportive therapy of a daily regimen following nausea. Furthermore, comparing the relative costs in the treatment of bone and soft tissue tumors, Kimura et al (20) demonstrated that a single dose of palonosetron was in no way inferior to continuous administration of multiple doses of granisetron. In the current analysis, palonosetron is also more cost-effective and is not inferior to granisetron when used in continuous administration regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the anti-emetic effects of granisetron last only a relatively short time when the drug is administered once or even twice per day; however, the effects of palonosetron persist over its long plasma elimination half-life, which facilitates continuous supportive therapy of a daily regimen following nausea. Furthermore, comparing the relative costs in the treatment of bone and soft tissue tumors, Kimura et al (20) demonstrated that a single dose of palonosetron was in no way inferior to continuous administration of multiple doses of granisetron. In the current analysis, palonosetron is also more cost-effective and is not inferior to granisetron when used in continuous administration regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with osteosarcoma or soft tissue sarcoma do not respond to NK-1 + 5-HT3 + DXM regimens, suggesting the efficacies of triple regimens for preventing CINV may be related to the cancer type [ 45 , 46 ]. We could not perform subgroup analysis of specific cancer types because data on cancer types were lacking in the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] In the previous study of chemotherapies including adriamycin plus cisplatin, ifosfamide plus etoposide, and AI for bone and soft-tissue sarcoma, effectiveness of the triplet therapy was examined, and AI was administered in 11 courses out of a total of 96 courses of chemotherapy. [26] Complete response rates of the prophylaxis in an acute, a delayed, and an overall period were 23%, 17%, and 7%, respectively, but specified antiemetic effect of the triplet therapy for AI has not been clarified. In the present study, we also observed that 85% of patients suffered nausea; even prophylaxis by a doublet therapy consisting of 3 mg of granisetron and 8 to 16 mg of DEX (the doublet group) was performed.…”
Section: Discussionmentioning
confidence: 99%